2017
DOI: 10.1038/cddis.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT-mediated upregulation of WDR5 promotes colorectal cancer metastasis by directly targeting ZNF407

Abstract: Colorectal cancer (CRC) is the third most common cause of cancer deaths, and has a high rate of liver and lung metastasis. Unfortunately, distant metastasis is the main barrier for advanced CRC therapy and leads to a very low survival rate. In this study, we identified WDR5, a vital factor that regulates vertebrate development and cell self-renewal and reprogramming, as a novel prognostic marker and therapeutic target for CRC patients. We demonstrate that WDR5 is upregulated in CRC tissues and promotes CRC met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 48 publications
6
63
0
Order By: Relevance
“…This is in agreement with previous studies, in which they reported that WDR5 was critically involved in hypoxia‐induced EMT and metastasis by abolishing mesenchymal gene expression in Fadu cells . In addition, WDR5 promoted EMT and metastatic behavior of colorectal cell in vitro and metastasis in xenograft mouse model by enhancing cell motility via directly regulating ZNF407 . Complementary, our findings also reveal that WDR5 overexpression tend to positively associate with cervical lymph node metastasis, although statistical significance was not achieved.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in agreement with previous studies, in which they reported that WDR5 was critically involved in hypoxia‐induced EMT and metastasis by abolishing mesenchymal gene expression in Fadu cells . In addition, WDR5 promoted EMT and metastatic behavior of colorectal cell in vitro and metastasis in xenograft mouse model by enhancing cell motility via directly regulating ZNF407 . Complementary, our findings also reveal that WDR5 overexpression tend to positively associate with cervical lymph node metastasis, although statistical significance was not achieved.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence has suggested that WDR5 functions as a putative oncogene by promoting cell proliferation, EMT, metastasis as well as chemoresistance in human cancer . Consistent with the pro‐proliferative roles of WDR5 in bladder, breast, and prostate cancer, our findings revealed that WDR5 depletion significantly inhibited cell proliferation, colony formation and cell cycle arrest in HNSCC cells.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Western blot was performed as previously described . CAF derived from patients with NPC and NPC cells treated with CM were lysed in radioimmunoprecipitation assay buffer containing protease inhibitor cocktail and phosphatase inhibitor cocktails (Roche, Basel, Switzerland) on ice, and the protein levels were quantified by using BCA protein assay kit (Dingguo Biotech Co., Beijing, China), according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%